2021
DOI: 10.1049/mna2.12100
|View full text |Cite
|
Sign up to set email alerts
|

Green preparation of nano‐silver aqueous solution using fructose and evaluation of its antibacterial potential for cut carnation flowers

Abstract: The green synthesis of nano‐silver (NS) has gained increasing attention owing to its cost‐effectiveness and environmental friendliness. Herein, a novel one‐step green preparation method of stable NS aqueous solution using Tollens reagent as the silver ion source, D‐fructose as the reduction agent, and polyvinyl pyrrolidone as the stabilizing and capping agent is reported. The prepared NS solution had a pH value of 7.10, with approximately spherical NS particles in the range of 13.95–87.36 nm. The resulting NS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The green synthesized Ag-NPs showed potent inhibitory activity against bacterial populations isolated from cut ‘Luoyang Hong’ stem in vitro ( Figures 4 , 5 ). Several studies have shown that biosynthesized Ag-NPs have an excellent ability to suppress bacterial reproduction in the vase solution and at the stem ends of cut flowers ( Carrillo-López et al., 2016 ; Pang et al., 2022 ). It was also reported that biosynthetic Ag-NPs using A. annua L. callus extracts could reduce bacterial blockage at the stem ends of A. annua , thus extending the vase life ( Xia et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The green synthesized Ag-NPs showed potent inhibitory activity against bacterial populations isolated from cut ‘Luoyang Hong’ stem in vitro ( Figures 4 , 5 ). Several studies have shown that biosynthesized Ag-NPs have an excellent ability to suppress bacterial reproduction in the vase solution and at the stem ends of cut flowers ( Carrillo-López et al., 2016 ; Pang et al., 2022 ). It was also reported that biosynthetic Ag-NPs using A. annua L. callus extracts could reduce bacterial blockage at the stem ends of A. annua , thus extending the vase life ( Xia et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still chemical reductants are expensive and can negatively affect the environment. Therefore, it is unsuitable for some research and applications ( Zakeri et al., 2021 ; Pang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%